Disparitas Afektif–Kognitif dalam Pembelajaran IPA Berorientasi Keberlanjutan Berbasis Kearifan Lokal Baduy - Eiftien Yuliar Rasyidin; Asri Widowati; Ismail Fikri Natadiwijaya (Postgraduate, University of Mataram, 2026)
Environmental crises require science education to develop not only environmental awareness but also students’ ability to reason about complex socio-ecological systems. This study aimed to analyze students’ Socio-Ecological Reasoning (SER) and Environmental Attitudes (EA) within contextual science learning based on Baduy local wisdom. A descriptive correlational quantitative approach was employed involving 30 seventh-grade students selected through purposive sampling. Data were collected using an essay-based SER test and a Likert-scale EA questionnaire and analyzed descriptively and inferentially using SPSS. The findings showed that students’ Environmental Attitudes were very high (M = 4.40), while Socio-Ecological Reasoning remained moderate (M = 3.07), indicating an affective–cognitive disparity. Pearson correlation analysis revealed a weak and non-significant relationship between both variables (r = 0.12; p > 0.05). This disparity suggests that contextual learning based on local wisdom effectively strengthens environmental values and awareness but has not fully facilitated systems thinking and higher-order reasoning skills, possibly because learning practices still emphasize value internalization more than analytical exploration. Therefore, science learning should integrate phenomenon-based and systems-oriented approaches that explicitly connect local wisdom with scientific inquiry to strengthen both affective and cognitive domains in sustainability-oriented education.